2023
DOI: 10.1177/17448069221147792
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture ameliorates knee osteoarthritis in rats via inhibiting NLRP3 inflammasome and reducing pyroptosis

Abstract: Objective: Knee Osteoarthritis (KOA), is the most common joint disease worldwide. The pathogenesis of KOA is complex and electroacupuncture (EA) is an effective therapy for KOA, but the mechanism remains unclear. In this study, we aim to investigate the potential therapeutic effect of EA on the rat model of KOA induced by monosodium iodoacetate (MIA) and its relationship with NLRP3 inflammasome by immunohistochemistry and western blot. Methods: KOA was induced by intra-articular injection of MIA (3 mg/50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous research has substantiated the effectiveness of EA in reducing cartilage damage and abnormal in ammatory responses linked to osteoarthritis [47]; however, the underlying cellular and molecular mechanisms are not yet fully understood. Recent ndings suggest that macrophages can activate cells in the immediate environment to release in ammatory cytokines [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has substantiated the effectiveness of EA in reducing cartilage damage and abnormal in ammatory responses linked to osteoarthritis [47]; however, the underlying cellular and molecular mechanisms are not yet fully understood. Recent ndings suggest that macrophages can activate cells in the immediate environment to release in ammatory cytokines [48].…”
Section: Discussionmentioning
confidence: 99%
“…The EA needles were inserted to a consistent depth. Alternating strings of dense-sparse frequencies (2/100 Hz EA stimulation, 15 min) were selected as reported previously ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“… (2) Reducing the expression of NLRP3, ASC, caspase-1, IL-1β and IL-18 in synovium. Zhang et al 107 EA Rats Reducing the contents of IL-1β and IL-18 and the expression of NLRP3, ASC and caspase-1. Central nervous system Regulating the descending pain control system Gao et al 110 Acupuncture Patients Enhancing the FC between dorsal RPN and the right putamen.…”
Section: Challenges and Perspectivementioning
confidence: 99%
“…Studies have demonstrated that EA could reduce the contents of IL-1β and IL-18 and the expression of NLRP3, ASC and caspase-1 in synovium of KOA rats. 106,107…”
Section: Effect Of Traditional Chinese Non-pharmacological Therapies ...mentioning
confidence: 99%